The effect of fiber oxidation on the friction and wear behaviors of short-cut carbon fiber/polyimide composites (eXPRESS Polymer Letters, 2007)
Pitch-based short-cut carbon fibers were treated by HNO3 oxidation, thereafter the treated (CFN) and untreated carbon fibers (CF) were incorporated into polyimide (PI) matrix to form composites. The carbon fibers before and after treatment were examined by Fourier Transform Infrared Spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscope (SEM). The friction and wear behaviors of PI composites sliding against GCr15 steel rings were evaluated on an M-2000 model ring-on-block test rig, which revealed that small incorporation of carbon fibers can decrease the friction coefficient and improve the wear resistance of PI composites, and that the reinforcement effect of treated carbon fibers was better than that of the untreated ones. It was found that the optimum content of carbon fibers is 15 wt% when a thin and continuous transfer film was formed on the counterpart surface during the friction process. With further increasing content of carbon fibers, the friction coefficient increased and the wear resistance reduced owing to the drop out of carbon fibers from PI matrix. Besides, the friction coefficient of the PI composites decreased and the wear resistance improved with increasing load, while for the pure PI, its wear resistance decreased drastically owing to the micro-melting and mechanical deterioration caused by friction heat under a higher load.